Elaboración de una bebida alcohólica utilizando dos variedades de agave; negro (Agave americano) y blanco (Furcraea andina) empleando Sacharomyces cerevisae en dos presentaciones (liofilizada y en pasta) en el sector de Cristo Rey Parroquia Once de Noviembre Cantón Latacunga Provincia de Cotopaxi - Arias Borja, Lourdes Marisol (2013)
The agave known in Ecuador as black sisal is a perennial originally from Mexico, and the Andean Furcraea known as white hemp is a plant native to the Ecuadorian Andes Venezuelans Colombo. And in the Ecuador is located along the boundaries forming inter-Andean corridor, is therefore that this research focused on the development of an alcoholic beverage from the agave white and black, meaning alcoholic beverages which are obtained based on fruits and vegetables by distillation and maceration….